2000
DOI: 10.1073/pnas.97.2.793
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral gene transfer of SERCA2a improves left-ventricular function in aortic-banded rats in transition to heart failure

Abstract: In human and experimental models of heart failure, sarcoplasmic reticulum Ca 2؉ ATPase (SERCA2a) activity is decreased, resulting in abnormal calcium handling. The disturbances in calcium metabolism have been shown to contribute significantly to the contractile dysfunction observed in heart failure. We investigated whether increasing SERCA2a expression can improve ventricular function in an animal model of heart failure obtained by creating ascending aortic constriction in rats. After 19 -23 wk of banding duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
295
2
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 493 publications
(324 citation statements)
references
References 38 publications
24
295
2
3
Order By: Relevance
“…Myocardial SERCA expression has been increased using gene therapy-based approaches in a number of small animal models, with varying success. 4,8,11 In conjunction with the improvement in contractile function, some deleterious aspects of increased calcium cycling have been observed, 12 such as impaired myocyte shortening at high SERCA1a activity, indicating the potential importance of dose optimization. Our study supports the notion of a beneficial effect of augmented SERCA expression in the failing heart.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial SERCA expression has been increased using gene therapy-based approaches in a number of small animal models, with varying success. 4,8,11 In conjunction with the improvement in contractile function, some deleterious aspects of increased calcium cycling have been observed, 12 such as impaired myocyte shortening at high SERCA1a activity, indicating the potential importance of dose optimization. Our study supports the notion of a beneficial effect of augmented SERCA expression in the failing heart.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 This was followed by evidence of improvement in contractile function in rodents with HF. 41,42 Finally, gene transfer of SERCA2a was found to be effective in large animal models of HF. 18 Most importantly in a preclinical model of HF, it was found that SERCA2a improved the contractile function in a dose-dependent manner.…”
Section: Serca2a Gene Therapymentioning
confidence: 99%
“…Furthermore, success in extremities does not necessarily correspond to success in the myocardium, which is a significantly more complex system. Viral clinical trials have examined a host of other genes, including a variety of fibroblast growth factors (FGF-2 and FGF-4), and sarcoplasmic reticulum Ca 2+ ATPase (SERCA2a) [130]. While little attention has been given to these genes in non-viral trials, either clinical or pre-clinical, they have significant therapeutic potential.…”
Section: Figurementioning
confidence: 99%